Aleitamento materno: uma reflexão sobre o papel do pai - Duarte, Cristiane Rodrigues (2014)
This study aims to reveal the feelings experienced by fathers during breastfeeding. It is a qualitative and descriptive research. Fifteen parents who had at least two children and experiences in breastfeeding process in Sorocaba were interviewed. The interviews were recorded at Santa Lucinda’s Hospital. The data organization was carried out using the Collective Subject Discourse. Reports were grouped into core ideas, totaling twenty-two speeches, among the most cited: little involvement in the breastfeeding process, knowledge of the importance of breastfeeding, satisfaction with the process of breastfeeding, feelings of abandonment and frustration, guidance received from other (lay), ignorance about the process of breastfeeding and its importance, lack of guidance from professionals about breastfeeding knowledge and breastfeeding technique, negative and positive experiences in the process of breastfeeding, fear and grief against the weaning process and reflecting on the breastfeeding process. The results shows that during this period, fathers demonstrates satisfaction and interest in participating with breastfeeding process, but also feel left out for being an intimate act between mother-child which is also not encouraged by health professionals in monitoring pre-birth, but some of them had active participation in this process . Nurse’s guidance is essential, either during the prenatal or postpartum period, because of the importance of incentives and guidance on the exclusive breastfeeding for the continuity of this process during the first six months of the baby’s life and to decrease the incidence of early weaning process